2017
DOI: 10.3897/nl.40.10062
|View full text |Cite
|
Sign up to set email alerts
|

Water ferns Azolla spp. (Azollaceae) as new host plants for the small China-mark moth, Cataclysta lemnata (Linnaeus, 1758) (Lepidoptera, Crambidae, Acentropinae)

Abstract: Abstract. Water ferns (Azolla spp., Azollaceae) are reported for the first time as host plants for the larvae of the small China-mark moth Cataclysta lemnata (Linnaeus) (Lepidoptera: Crambidae: Acentropinae) in rice fields and waterways of northern Iran. Cataclysta lemnata is a semi-aquatic species that has been recorded to feed on Lemnaceae and a few other aquatic plants. However, it has not been reported before on Azolla spp. Larvae use water fern as food source and shelter and, at high population density in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(25 reference statements)
2
5
0
1
Order By: Relevance
“…More work is needed to verify whether these South American strains represent a new species of Azolla . The phylogenetic position of the Anzali accession analyzed here was consistent with the observations of several distinct-looking Azolla in the Anzali lagoon (Farahpour-Haghani et al, 2017 ), and suggested that not only A. filiculoides may have been released as nitrogen biofertilizer.…”
Section: Discussionsupporting
confidence: 89%
“…More work is needed to verify whether these South American strains represent a new species of Azolla . The phylogenetic position of the Anzali accession analyzed here was consistent with the observations of several distinct-looking Azolla in the Anzali lagoon (Farahpour-Haghani et al, 2017 ), and suggested that not only A. filiculoides may have been released as nitrogen biofertilizer.…”
Section: Discussionsupporting
confidence: 89%
“…Anzali ferns were not A. filiculoides but related to species from Uruguay and Southern Brazil which did not cluster with, ( Figure 2) and did not have the single-celled papillae of the traditional A. caroliniana species (Pereira et al, 2001; Supplemental Figure 3). Position of the Anzali accession was consistent with observations of distinct Azolla ferns in the Anzali lagoon (Farahpour-Haghani et al, 2017), and suggests that not only A. filiculoides may have been released as nitrogen biofertilizer.…”
Section: Red-dominated Light Suppresses Formation Of Dissemination Stsupporting
confidence: 84%
“…Azolla is a genus of 5 to 8 varieties of suspended marine plants that previously belongs to family Saliviniaceae [7], while modern researches put Azolla in family Azollaceae [8] which is a family of heterosporous ferns in the order Salviniales [9]. Azolla also was known as Mosquito ferns or Duckweed that create a mutual partnership with cyanobacteria with the ability to fix Nitrogen [10,11,12].…”
Section: Introductionmentioning
confidence: 99%